A heterogenous Cournot duopoly model with discrete delay and externalities - Averbuj, Corina Gabriela (2018)
In this article, we consider a nonlinear continuous-time model with discrete delays and externalities. We study the dynamic competitors’s behavior, when they are heterogeneous in determining the output decisions. We have determined a unique positive equilibrium solution and we have applied mathematical techniques (Nyquist criterion) to estimate the range of the delays for which the equilibrium state remains asyntotically stable.